'Extended tibia osteotomy': a technical tip for removal of incarcerated reamer with broken guide wire bead during tibia nailing and literature review. Issue 3 (8th March 2022) - Vatsya, Pulak; Mittal, Samarth; Karpe, Aashraya; Trikha, Vivek
Abstract : Intramedullary nailing has become a standard of care for tibia fractures. Reaming is an essential part of this technique due to its multiple advantages like a better fit and earlier union. In young bone, with a narrow cortical canal, incarceration and breakage of reamer is a possibility. This can be removed with a ball-tip guidewire. In our case, the broken incarcerated reamer was complicated by a broken ball-tip of the guidewire, leading us to invent a novel medial tibial osteotomy window for the reamer removal. This can be a handy tool for a stuck surgeon intraoperatively.